Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
We have to multiply given (3-2i)(3+2i)
(3-2i)(3+2i)=9-6i+6i+4i^2
9+4i^2
We know that i^2=-1, so lets substitute it
9+4*(-1)=9-4=5
(3-2i)(3+2i)=9-6i+6i+4i^2
9+4i^2
We know that i^2=-1, so lets substitute it
9+4*(-1)=9-4=5
Answer:
the product (3-2i)(3+2i) is, 13
Step-by-step explanation:
Using the identity rule:
[tex](a+b)(a-b) = a^2-b^2[/tex]
Given that:
[tex](3-2i)(3+2i)[/tex] ...[1]
here, i is the imaginary part.
[tex]i^2 = -1[/tex]
Apply the rule on [1] we have;
[tex](3)^2-(2i)^2[/tex]
⇒[tex]9-(4i^2)[/tex]
⇒[tex]9+4[/tex]
Simplify:
13
Therefore, the product (3-2i)(3+2i) is, 13
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.